Kid activists : true tales of childhood from champions of change - Stevenson, Robin, 1968-; Steinfeld, Allison (Philadelphia, PA : Quirk Books, 2019)
A collection of anecdotes from the childhoods of famous activists, including Emma Watson, Martin Luther King Jr., Malala Yousafzai, and others.
Includes bibliographical references (p. 214-218) and index.
Booklist
Kirkus Review
School Library Journal
Booklist, September 2019
Kirkus Review, August 2019
Keywords: Civil rights movements -- United States -- History -- Juvenile literature; Civil rights workers -- Juvenile literature; Political activists -- Juvenile literature; Civil rights movements -- History; Civil rights workers; Political activists; Civil rights movements -- History; Civil rights workers; Political activists; Anecdotes